PERBANDINGAN METODE SHARED STORAGE DAN METODE DEDICATED STORAGE PADA PENEMPATAN DAN PENYUSUNAN BARANG DI GUDANG SPAREPARTS PT INDONESAI ASAHAN ALUMINIUM (PERSERO) - Yetti Meuthia Hasibuan; Abdul Azis Syarif; Denny Walady; Rafiqi Pratama; Hadad Alwi Hakim Hasibuan (Jurnal Simetri Rekayasa, 2022)
PT Indonesia Asahan Aluminium (Persero) is one of the State-Owned Enterprises (BUMN) engaged in aluminum smelting and is the only company engaged in the aluminum smelting industry in Indonesia. This research was conducted in the spare parts warehouse, where the problem is that the layout of the warehouse is still random and not neat, causing disruption of the storing issuing process and activities in the warehouse. Shared storage and dedicated storage is a methods of redesigning the storage layout to get a repair design. Then to get the optimum design results, the calculation results of the two methods are compared to obtain an efficient improvement design from the actual conditions. The results of the shared storage design obtained a mileage minimization of 1,133.18 m. Dedicated storage can minimize mileage by 394.59 m. This distance has decreased from the previous distance the initial layout distance was 5,639.00 m. So that the optimal method used is the shared storage method with a distance reduction of 4,505.82 m of material handling travel from the initial conditions. With this research, it is hoped that the spare parts warehouse will be neater and more organized so as to facilitate activities in storing and picking up goods, and can save used blocks.